Development, Characterization, and Evaluation of PSMA-Targeted Glycol Chitosan Micelles for Prostate Cancer Therapy. (15th October 2014) - Xu, Jing; Yu, Jingmou; Xu, Xiao; Wang, Liangliang; Liu, Yonghua; Li, Lixin; Zhao, Jianguo; He, Ming
Abstract : Prostate cancer-binding peptides- (PCP-) modified polymeric micelles were prepared and used for the treatment of prostate-specific membrane antigen- (PSMA-) expressing prostate cancer in a target-specific manner. Cholesterol-modified glycol chitosan (CHGC) was synthesized. PCP-conjugated CHGC (PCP-CHGC) micelles were fabricated and characterized. The degree of substitution was 5.2 PCP groups and 5.8 cholesterol groups per 100 sugar residues of glycol chitosan. The critical aggregation concentration (CAC) of PCP-CHGC copolymer was 0.0254 mg/mL. Doxorubicin (DOX) was chosen as a model antitumor drug. The DOX-loaded micelles were prepared by an o/w method. The mean diameter of DOX-loaded PCP-CHGC (DOX-PCP-CHGC) micelles was 293 nm determined by dynamic light scattering (DLS). DOX released from drug-loaded micelles was in a biphasic manner. DOX-PCP-CHGC micelles exhibited higher cytotoxicity in vitro against PSMA-expressing LNCaP cells than DOX-loaded CHGC (DOX-CHGC) micelles. Moreover, the cellular uptake of DOX-PCP-CHGC micelles determined by confocal laser scanning microscopy (CLSM) and flow cytometry was higher than that of DOX-CHGC micelles in LNCaP cells. Importantly, DOX-PCP-CHGC micelles demonstrated stronger antitumor efficacy against LNCaP tumor xenograft models than doxorubicin hydrochloride and DOX-CHGC micelles. Taken together, this study provides a potential way in developing PSMA-targeted drug delivery system for prostate cancer therapy.